Associations between singing to babies and symptoms of postnatal depression, wellbeing, self-esteem and mother-infant bond. (April 2017) - Fancourt, D.; Perkins, R.
Highlights: There is growing research into the benefits of singing for mental health and wellbeing. To date, little quantitative research has looked at benefits of singing for new mothers. Data show associations between singing to babies and fewer symptoms of postnatal depression. Data also show associations with enhanced wellbeing, self-esteem and mother-infant bond.